THE IMPLICIT CONCEPTION OF MUSIC IN BOETHIUS' "DE CONSOLATIONE PHILOSOPHIAE" - Кагало, Аліна (Ukrainian Cultural Studies, 2023)
The paper is an attempt to demonstrate the possibility and necessity of an implicit conception of music in Boethius. An explicit conception is something that is obviously present in a text. That is what is usually studied within the 'history of ideas'. Contrary to this, an implicit conception is an unconscious picture of the author's world, in which the basic concepts of explicit conception are grounded. Therefore, the implicit conception is a condition for the possibility of any explicit text. So, the well-known text of Boethius' "De institutione musica", which but replicates mostly Pythagorean views of music, is an explicit conception. We chose "De consolatione philosophiae" as the most representative and semantically loaded text by Boethius to look for his implicit conception of music. It is based on different but unconscious grounds. We read this text to look for unconscious semantics associated with the concept. Thus, the unconscious semantics of music should be studied using the psychoanalytic approach in its broadest sense. The approach asks for the cues of connotations of the terms used by Boethius. The history of reception of the text, including different translations, can show the way. We should bear in mind, too, that the text we read is the record of an internal dialogue, which brings forth a different ontological horizon. Besides, we should see the text as a texture of signs and symptoms, pointing to unconscious notions Boethius had developed. The necessity of such an approach and the relevance of the results obtained within it are discussed in the article. The guidelines for the reconstruction of the implicit conception of music in Boethius are outlined and the elements of this conception are proposed. By further development of the method demonstrated and applied in this paper we shall be able not only to understand Boethius better, but we can reveal the intrinsic contents of the basic concepts describing the realities culture scholars are working with.
Keywords: music; Boethius; implicit conception; psychoanalytic approach; text